2006
DOI: 10.1590/s1678-77572006000500010
|View full text |Cite
|
Sign up to set email alerts
|

Influence of different methods of cervical flaring on establishment of working length

Abstract: Objective:to investigate the influence of three different rotary systems for cervical flaring on establishment of the real working length. Material and methods: Thirty mandibular first molars were submitted to conventional endodontic access and initial working length measurement, followed by irrigation/suction of the pulp chamber with 5% sodium hypochlorite. Teeth were randomly divided into 3 groups (n=10) and cervical flaring of the mesiobuccal canals were performed using one of the following instrument syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 9 publications
1
11
0
1
Order By: Relevance
“…Insofar 1 mm short of the radiographic apex, the mean minor diameter is around 0.22 mm and larger around 0.33 mm. 26 In the present study it was found that after the enlargement of the cervical and middle thirds, regardless of the technique, the diameter of 0.316 mm, which is consistent with the results found by Kuttler (1955) 24 and Green 25 (1958). Thus, starting canal preparation with a small diameter file (# 10 or 15) would make the cleaning and shaping of that root canal unsatisfactory due to inadequate adaptation of the file.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Insofar 1 mm short of the radiographic apex, the mean minor diameter is around 0.22 mm and larger around 0.33 mm. 26 In the present study it was found that after the enlargement of the cervical and middle thirds, regardless of the technique, the diameter of 0.316 mm, which is consistent with the results found by Kuttler (1955) 24 and Green 25 (1958). Thus, starting canal preparation with a small diameter file (# 10 or 15) would make the cleaning and shaping of that root canal unsatisfactory due to inadequate adaptation of the file.…”
Section: Discussionsupporting
confidence: 92%
“…Nickeltitanium rotary files type Orifice Openers also had a greater reduction in the length of labor, compared with GatesGlidden drills. 26 Different results were obtained by Davis et al (2002) 22 who associated hand files to Gates-Glidden drills, getting greater decrease in the length of labor. These drills perform the rectification of the root canal, while the nickel-titanium rotary files are characterized remain centered within the root canal during instrumentation, minimizing root canal straightening, causing minimal changes in root canal configuration, keeping the original form of the root canal.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Cervical preparation contributes toward establishing an appropriate anatomic diameter of the root canal (12,13) and determines a stable working length. Additionally, this procedure can facilitate the action of endodontic instruments in the apical third (14), allowing for the effective cleaning of this region (15,16). A suitable preparation of the cervical third enables direct access of the instrument within the canal, thereby decreasing possible accidents during the biomechanical preparation (17), proper penetration of irrigating solutions in the apical third (18), and a satisfactory root obturation (19).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this coronal widening reduces the risk of canal anatomy modification. There is a lack of information about coronal third canal morphology changes produced by orifice shapers instruments in comparison to other features of these instruments as changes in working length or influence in the behaviour of the following shaping instruments (6,7). The goal of orifice openers instruments is to widen the root canal coronal third in order to permit a better access of shaping instruments to the medium and apical root canal thirds.…”
Section: Introductionmentioning
confidence: 99%